Pharmacological inhibition of porcupine induces regression of experimental skin fibrosis by targeting Wnt signalling. Issue 4 (2nd February 2017) - Chen, Chih-Wei; Beyer, Christian; Liu, Jun; Maier, Christiane; Li, Chun; Trinh-Minh, Thuong; Xu, Xiaohan; Cole, Stuart H; Hsieh, Mindy H; Ng, Nicholas; Althage, Alana; Meeusen, Shelly; et al.
Abstract : Objectives: Wnt signalling has been implicated in activating a fibrogenic programme in fibroblasts in systemic sclerosis (SSc). Porcupine is an O-acyltransferase required for secretion of Wnt proteins in mammals. Here, we aimed to evaluate the antifibrotic effects of pharmacological inhibition of porcupine in preclinical models of SSc. Methods: The porcupine inhibitor GNF6231 was evaluated in the mouse models of bleomycin-induced skin fibrosis, in tight-skin-1 mice, in murine sclerodermatous chronic-graft-versus-host disease (cGvHD) and in fibrosis induced by a constitutively active transforming growth factor-β-receptor I. Results: Treatment with pharmacologically relevant and well-tolerated doses of GNF6231 inhibited the activation of Wnt signalling in fibrotic murine skin. GNF6231 ameliorated skin fibrosis in all four models. Treatment with GNF6231 also reduced pulmonary fibrosis associated with murine cGvHD. Most importantly, GNF6231 prevented progression of fibrosis and showed evidence of reversal of established fibrosis. Conclusions: These data suggest that targeting the Wnt pathway through inhibition of porcupine provides a potential therapeutic approach to fibrosis in SSc. This is of particular interest, as a close analogue of GNF6231 has already demonstrated robust pathway inhibition in humans and could be available for clinical trials.